Cochonilhas-farinhentas associadas à videira na Serra Gaúcha, bioecologia e controle de Planococcus citri (Risso, 1813) (Hemiptera: Pseudococcidae). - Morandi Filho, Wilson José (2008)
Mealybugs of the Pseudococcidae family have been reported as causing direct damage (losses in production) and indirect (transmission of virus) in vineyards. Few information is available about the species occuring in the vineyards and the bioecology of pseudococidae in Brazil. In this work we identified the species of Pseudococcidae associated with vineyards in Serra Gaúcha region; studied the biology and determined the thermal requirements of Planococcus citri estimating the number of annual generations in different producing regions and, evaluated the effect of insecticides alternative to phosphorous for the control of the species. P. citri, Planococcus minor, Pseudococcus viburni, Pseudococcus maritimus, Dysmicoccus brevipes were found associated with the vineyards in the region. P. citri was the most abundant species. The biology of P. citri was studied in leaves of the vine cultivars Cabernet Sauvignon, Italy and Isabel, in fruits of cultivar Italy, in roots of cultivars Isabel and in 101-14 and IAC-572 rootstocks. On roots of the rootstock IAC-572, P. citri was unable to complete the life cycle. The average period from egg to adult males was 24.63 ± 0.10 days with viability of 32% while females lasted 32.00 ± 0.11 days with viability of 56% when fed on leaves of vine cultivars. In roots, the cycle duration of the females and males was 32.45±0.19 and 29.50±0.51 days, respectively. The lowest viability of the nymphal cycle was found in roots of Isabel, 8.1% for females and 4.0% for males while the high viability was obtained in leaves of Cabernet Sauvignon, 62.7% and 32.7% for females and males, respectively. The mealybug P. citri completed the life cycle in leaves of the vine cultivars Cabernet Sauvignon, Italy, Isabel; roots of the rootstocks 101-14 and Isabel. The Italy grape berries allowed the nymphal development of P. citri, however the adults were infertile. The roots of the door graft IAC-572 are immune to P. citri. The speed of development of P. citri increases with temperature elevation. The temperatures of 25°C and 28°C were the most appropriate for the insect development. The threshold temperature and thermal constant for the full cycle (egg-adult) of P. citri in vine leaves of the cultivar Italy was 8.16°C and 574.71 degree days, respectively. Based on the thermal requirements, we estimated that the insect may have 5.7 annual generations in Bento Gonçalves (RS), 6.2 in Bagé (RS), 6.9 in São Lourenço (MG), 7.9 in Londrina ( PR), 9.7 in Jales (SP) and 11.5 in Petrolina (PE). In the assessment of insecticides for the control of the insect, the neonicotinoids acetamiprid (0.60 g ai / plant), imidacloprid (0.70 g ai / plant) and thiamethoxam (0.75 g ai plant) were effective in the control of P. citri in vine plants with 1 year old. In adult plants (15 years) the same treatments and doses were not effective to pest control. Foliar spray of acetamiprid (6 20 ia/100L), imidacloprid (7 ia/100L), thiamethoxam (7.5 g ia/100L) and insect growth regulators buprofezin (25 ia/100L) and pyriproxyfen (10g ai 100L) were not effective to control P. citri.